Composite-fabric-based structure-integrated energy storage system. (15th April 2023) - Choi, Joo-Seung; Park, Hyun-Wook; Noh, Jung-Eon; Cha, Jihun; Jang, Woo-Hyeok; Kim, Chun-Gon
Abstract: A structure-battery-integrated energy storage system based on carbon and glass fabrics is introduced in this study. The carbon fabric current collector and glass fabric separator extend from the electrode area to the surrounding structure. This system provides stable and high electrochemical performance under the mechanical loading of the composite structural battery. A thermoplastic tape melted into the fabrics separates the battery and structural parts to prevent penetration of epoxy into the battery part during autoclave molding and leakage of liquid electrolyte. Furthermore, a stainless-steel film blocks moisture penetration in the direction of the thickness. The electrochemical characteristics and mechanical stability of the structural battery were evaluated using a galvanic cell tester. The initial capacity of the structural battery was approximately 125 mAh/gLFP, and it exhibited steady cycling characteristics with a capacity of 110 mAh/gLFP for up to 50 charging/discharging cycles. The structure-integrated battery exhibited an energy density of over 25 Wh/kgstr, stable electrochemical performance, and load-bearing characteristics even when some of the battery components were subjected to tensile strain beyond the 1% level.